Determination of the glycemic index of varying proportions of a novel formulation of staple cassava flour - Gari - Egba, Simeon C.; Adimuko, Goodluck C; Akokwu, Gospel C.; Omeoga, Humphrey C.; Okafor, Polycarp N. (Journal of Scientific Agriculture, 2017)
This study was carried out to determine the glycemic index of coconut-enriched gari which was fermented at various durations. A total of 18 apparently healthy subjects participated in the study. The determination of total carbohydrate, crude fibre and available carbohydrate, followed by glycemic index was performed on six samples of the coconut gari using the standard operating procedure. The coconut gari samples (48 hours fermentation) gave mean glycemic index values ranging from 81.96 ± 3.42 - 84.96 ± 4.90 while the 72 hours fermentation gave a mean range of 74.34 ± 2.24 – 82.04 ±5.40. The samples were subjected to statistical analysis using ANOVA and found to be non-significantly (p > 0.05) different when compared to each other. The low G.I rating observed in coconut gari fermented for 72 hours is an indication that the food may be good for consumption as a staple except with under some exceptional conditions. This study suggests that extensive fermentation of gari enriched with coconut could be nutritionally appropriate for diabetics.